2019
DOI: 10.1126/scirobotics.aax8336
|View full text |Cite
|
Sign up to set email alerts
|

Floating magnetic microrobots for fiber functionalization

Abstract: Because minimally invasive surgery is increasingly used to target small lesions, demand is growing for miniaturized tools—such as microcatheters, articulated microforceps, or tweezers—that incorporate sensing and actuation for precision surgery. Although existing microfabrication techniques have addressed the construction of these devices, accurate integration and functionalization of chemical and physical sensors represent major challenges. This paper presents a microrobotic platform for the functionalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 39 publications
0
50
0
Order By: Relevance
“…This ratio will be studied to understand how many electrodes an implant can accommodate and the diameter of these electrodes to allow the implant to fully recover shape. Conversely, we can explore other alternatives to include electrodes in our SMP‐based CI, such as co‐drawing SMP and low temperature melting metal or introducing electrodes in the implant as suggested by Barbot et al [ 32 ] The results also showed a degree of variability that can be explained in part by how the material molds or collapses around the metal electrode during the molding stage, as shown by the implants tested to assess the stiction effect, which laid closer to the calculated fit line. The effect of the electrode during molding was also noticed when we compared the average initial angle after molding for the implants with and without an electrode used in this work experiments, which was 320° ( n = 30) and 282° ( n = 9), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This ratio will be studied to understand how many electrodes an implant can accommodate and the diameter of these electrodes to allow the implant to fully recover shape. Conversely, we can explore other alternatives to include electrodes in our SMP‐based CI, such as co‐drawing SMP and low temperature melting metal or introducing electrodes in the implant as suggested by Barbot et al [ 32 ] The results also showed a degree of variability that can be explained in part by how the material molds or collapses around the metal electrode during the molding stage, as shown by the implants tested to assess the stiction effect, which laid closer to the calculated fit line. The effect of the electrode during molding was also noticed when we compared the average initial angle after molding for the implants with and without an electrode used in this work experiments, which was 320° ( n = 30) and 282° ( n = 9), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The actuating magnetic field itself can be supplied using electromagnetic coils or permanent magnets, but the latter option was incorporated into our system due to space constraints and its simplicity of implementation. Permanent magnets have been used for actuation in a variety of other robotic systems, including helical microrobot platforms [ 47 , 48 , 49 ], a microrobotic system for aligning floating electronic circuits to fibers in a wet transfer process [ 50 ], and a larger system involving magnetic capsule endoscopes [ 51 ]. More recently, point-to-point closed-loop motion control of magnetically driven screws actuated using permanent magnets was demonstrated within an agar gel tissue phantom [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these approaches, there are also some other techniques specifically for integrating sensors on readymade soft devices, e.g., laser‐tuned selective transfer printing [ 306 ] and wet transfer process. [ 307 ] Among them, the laser‐tuned selective transfer printing technology can also be used for the assembly and reconstruction of soft magnetic robots, [ 308 ] through which we can perceive its potential of being used to construct complex 3D soft structures in a layer‐by‐layer manner. Introducing them as a postprocessing step or directly integrating them with other methods can be considered in future.…”
Section: Fabrication Techniquesmentioning
confidence: 99%